Ecommerce shipping solution for mobile platform - Wong, Jun Wei (2020)
This project is about an ecommerce shipping solution for mobile platform that aims to reduce the shipping fee charge and also decrease the time waiting for the buyer to receive their parcel. Nowadays, the innovation of the internet made everyone can become a seller on the internet. People starting to promote their products and sell it through a social networking platform because there is no any charging fee with using social networking platforms to sell an item. However, this way also brings a problem to the seller. They need to find a courier service company that offers a cheaper price to help them to ship the item for their buyer. Therefore, ecommerce shipping solution for mobile platform is planned to develop in order to help the online seller solve their problem. ecommerce shipping solution for mobile platform allows user to find out the nearby courier delivery companies that located around them. Besides, the estimated shipping fee and distance between courier delivery companies also will be listed together on the map to let the seller know which courier delivery company is the closest and provides the cheapest shipping price. Lastly, this project also helps the seller find the nearby active driver and send their parcel to the selected courier company.